Pharmacokinetics and bioequivalence of two formulations of mifepristone tablets in healthy Chinese subjects under fasting conditions: a single-center, open, randomized, single-dose, double-period, two-sequence, crossover trial - Yufeng Yan; Xiaoshan Zhu; Ping Dong; Cheng Liu; Lingqing Lu; Liyan Zeng; Guiying Chen; Xianmin Meng; Xianmin Meng; Min Liu (Frontiers Media S.A., 2024)
ObjectiveA bioequivalence (BE) study was performed to evaluate the pharmacokinetics, safety, and bioequivalence of two formulations of mifepristone tablets in healthy Chinese volunteers under fasting conditions.MethodsA single-center, open, randomized, single-dose, double-period, two-sequence, crossover study in healthy subjects under fasting conditions was performed. The subjects received a single fasting dose of mifepristone (10 mg/tablet) during the first and second periods, followed by a 14-day washout period, during which frequent pharmacokinetic (PK) sampling occurred up to 120 h. The pharmacokinetic parameters of mifepristone were calculated based on the plasma drug concentration-time profile. Primary endpoints were the BE of major pharmacokinetic parameters (AUC0-t and AUC0-∞) and the maximum observed serum concentration (Cmax). Secondary endpoints were safety parameters.ResultsForty subjects (34 male and 6 female subjects) were randomly assigned to treatment, with 39 completing the two-period study. After the single administration of mifepristone tablets (test preparation vs. reference preparation) under fasting conditions, the geometric mean ratios (GMRs) of Cmax, AUC0-t, and AUC0-∞ were 98.76%, 104.28%, and 104.83%, respectively. The primary metabolites of mifepristone (RU42633 and RU42698),the GMRs of Cmax, AUC0-t, AUC0-∞ were 102.33% and 100.97%, 103.17% and 103.71%, 104.02% and 103.84%, respectively. Similarly, for another metabolite of mifepristone (RU42698), the GMRs of Cmax, AUC0-t, and AUC0-∞ were 100.97%, 103.71%, and 103.84%, respectively. All 90% confidence intervals (CIs) for the test/reference AUC ratio and Cmax ratio were within the acceptable range (80%-125%) for BE, which met the requirements of bioequivalence. No serious adverse events (AEs) occurred, and all AEs were classified as level 1 or 2.ConclusionThe PK parameters of mifepristone and its metabolites (RU42633 and RU42698) were measured using the (GMRs) of AUC0-t, AUC0-∞, and Cmax and were similar between the test and reference drug. The two formulations of mifepristone showed good tolerability and a similar safety profile.Clinical Trial Registrationchinadrugtrials.org.cn, identifier CTR20182413.